Urban geology: educational proposal for Geoscience. a case study from the inner city of Athens, Greece. - Kontokostas, George; Antonarakou, Asimina; Fountopoulou, Marisa; Drinia, Hara; Lozios, Stelios (Bulletin of the Geological Society of Greece, 2020)
The limited exploitation and low understanding of geological notions, in modern education in physical sciences, motivated the planning of research procedures about the understanding of rock formations, of recognizing rocks, of informing about geological and hydrographic potential, for students of secondary school of Attica, using techniques entailed in the scientific/educational methodology by inquiry, suggesting educational walking paths through the historical center of Athens. Selected places of the walk trail served our educational aims. Via the educational intervention, students improved their understanding of geological notions, their creativity, their cooperation and their critical thinking. The educational walk trail motivated the students’ interest in the science of geology.